144 Evaluation of existing practice: denosumab for hypercalcaemia of malignancy. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Kavanagh, Emily; Woods, Elizabeth; Brown, Jolene; Dewhurst, Felicity; Waterfield, Kerry; Rowley, Grace; Pickard, Jonathan; Wakefield, Donna
Abstract : Background: Hypercalcaemia of malignancy (HoM) is a burdensome problem affecting up to 44% of patients with advanced cancer. The standard of care is treatment with an intravenous bisphosphonate. Bisphosphonates are contraindicated in renal failure. Denosumab is a monoclonal antibody that inhibits osteoclast differentiation and activity. Licensed for the prevention of skeletal related events in patients with bone metastases, Denosumab has been noted to cause hypocalcaemia in previously normocalcaemic patients. Denosumab is administered by subcutaneous injection and is safe in renal failure. Ad hoc use of Denosumab for HoM has been observed in the palliative care setting. We aimed to evaluate existing practice around the use of Denosumab for HoM by palliative medicine consultants in the North East of England. Methods: We constructed an online survey informed by a targeted literature review. The survey was disseminated electronically to all consultants in the North East regional palliative care physicians' group. An email reminder was sent after 7 weeks. The survey was closed after 8 weeks. Results: There were 28 respondents out of a possible 34. Eleven (39.3%) had used Denosumab for HoM. Of these, all used Denosumab for bisphosphonate refractory hypercalcaemia. There was some experience where bisphosphonates were contraindicated due to renal impairment. One patient was administered Denosumab at home. Four respondents used Denosumab in repeated doses for the same patient. Eight respondents reported that Denosumab successfully reduced serum calcium; three reported 'sometimes'. Doses varied between 60 mg and 120 mg. All consulted with another specialty (oncology 90.9%) prior to using Denosumab. There was high variability in the duration to re-test serum calcium. Two respondents encountered hypocalcaemia. There were no other adverse effects reported. Conclusions: Our results describe regional experience in the use of Denosumab. There was a wide variation in dosing and monitoring practices. The development of evidence-based guidance is strongly recommended.